Representasi Perjuangan Seorang Ibu Immigrant dalam Film Mrs Chatterjee Vs Norway - Sukma Radila; Tessa Shasrini (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Films are included in audio-visual media which are made with the aim of being entertainment media, educational media, politics and propaganda media. One of the films shown as entertainment media and also educational media is the film Mrs Chatterjee vs Norway, which tells the story of an immigrant mother's struggle to restore custody of her child. In this research, the method used is descriptive qualitative with John Fiske's semiotic theory. Semiotics is a science that studies signs. This research aims to find the meaning of a sign that shows a mother's struggle by using John Fiske's three levels of semiotics, namely the level of reality, representation and ideology. This research has revealed that the film Mrs Chatterjee vs Norway has shown a strong representation of the struggles of an immigrant mother living in a foreign country. In the process, the researcher will connect several scenes contained in that show the struggle of an immigrant mother with John Fiske's semiotic theory. Judging from Debika Chatterjee's character, it really depicts a mother's struggle for her children, and also illustrates how strong a woman is in facing every problem and obstacle she goes through in life alone. The results of this research are 8 scenes that show the struggle of an immigrant mother who moves to a foreign country because she joins her husband who demands a job which results in a problem of cultural differences which results in the mother having to try to restore custody of her child. From the research that has been carried out, researchers draw the conclusion that a mother will do anything for her own child, no matter what obstacles she goes through, a mother will still fight for her child, even a mother will sacrifice her life for the sake of her child.